Alterations of the CD58 gene in classical Hodgkin lymphoma. Issue 10 (21st July 2015) - Schneider, Markus; Schneider, Stefanie; Zühlke‐Jenisch, Reina; Klapper, Wolfram; Sundström, Christer; Hartmann, Sylvia; Hansmann, Martin‐Leo; Siebert, Reiner; Küppers, Ralf; Giefing, Maciej
<x xml:space="preserve">Abstract</x> Immune evasion plays a central role in the pathophysiology of classical Hodgkin lymphoma (cHL). As mutations of the CD58 gene contribute to immune evasion of diffuse large B cell lymphoma tumor cells, we studied whether alterations of the CD58 gene also occur in Hodgkin and Reed/Sternberg (HRS) cells of cHL. Single nucleotide polymorphism chip analysis revealed homozygous deletions within the CD58 gene in two cHL cell lines (SUP‐HD1 and U‐HO1). Sequencing of the CD58 gene in seven cHL cell lines disclosed in addition a homozygous splice site mutation in cell line KM‐H2. None of the three mutated lines expressed CD58 protein on their surface. Thus, three of seven cHL cell lines analyzed harbor destructive CD58 mutations. Molecular analysis of isolated HRS cells from 10 primary cases of cHL; however, did not reveal any case with a CD58 mutation. A FICTION study indicated heterozygous deletions of CD58 in 3 of 13 cHL analyzed. Overall, we report frequent inactivating mutations of CD58 in cHL cell lines, but their rare occurrence in primary HRS cells. As the three cHL cell lines with CD58 mutations were all established from HRS cells located in pleural effusions, i.e., outside the normal lymph node microenvironment, in end‐stages of the disease, CD58 inactivation in cHL might be predominantly prevalent to such situations. © 2015 Wiley Periodicals, Inc.